Answer to Question #14627 in Trigonometry for Danielle
Simplify:
2x^2y^4*4x^2y^4*3x
------------------------
3x^-3y^-2
1
2012-10-19T08:47:39-0400
2x^2y^4 * 4x^2y^4 * 3x
---------------------------- =
3x^-3y^-2
2 * x^2y^4 * 4 * x^2y^4 * 3 * x
= ------------------------------------ =
3 * x^-3y^-2
8 * x^2y^4 * x^2y^4 * x
= --------------------------- =
x^-3y^-2
8 * x^(4y^4 + 1)
= ------------------- = 8 * x^(4y^4 + 3y^2 + 1)
x^-3y^-2
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment